Detection of Mycoplasma hominis and Ureaplasma urealyticum in Blood Samples of Recurrent Pregnancy Loss in Women by Polymerase Chain Reaction. - Chiad, Ishraq A. (Journal of the Faculty of Medicine Baghdad, 2013)
Background: Genital mycoplasma are implicated in pelvic inflammatory disease, puerperal infection, septic abortion, low birth weight, nongonococcal urethritis and prostatitis as well as spontaneous abortion and infertility in women. Objective: We aimed to find a relationship between repeated abortions of unknown etiology and caused of Mycoplasma hominis andUreplasma urealyticum. Methods: one hundred sixty cases, (15-49 years old) with history of recurrent abortion, intrauterine fetal death andneonatal death (after exclusion of other factors as cause abortion), and hundred women with normal pregnancy outcome with the same age were chosen as controls. M. homini and U. urealyticum were detected in blood by PCR. Result: M. homini could be detected in 12\160 (7.5%) in women with pregnancy losses, but was not detected in control group. U. urealyticum could be detected in 64\160 (40%) in patient group and 4\100 (4%) in control group. The rapid detection of M. homini andU. urealyticum by PCR in pregnancy loss women could be important and necessary. The detection rate of M. homini andU. urealyticum in young women age (20-29 years) was higher than the others. Significant difference was observed in patients with three or four abortions compare with 2 or one abortion in addition to history of adverse outcome. Conclusion: the role M. homini andU. urealyticum in the etiology of pregnancy losses was proposed.